DESAIN KONVERTER SEPIC UNTUK METODE PENGEREMAN REGENERATIF EKSITASI MANDIRI PADA MOTOR INDUKSI 3 FASA SEBAGAI PENGISIAN BATERAI - Muhammad Alman Wadi; Waru Djuriatno; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
Today the development of electric vehicles is starting to be widely used compared to fossil fuel vehicles, one example is the electric train. An electric train is a train whose propulsion system is an electric motor. An induction motor is an alternating current (AC) electric motor that operates on the basis of induction of the stator's magnetic field into the stator. Here the motor rotor current causes a magnetic field generated by the rotation of the rotor and the stator current. One of the important parameters contained in the vehicle is braking. The regenerative braking method was used in this study where the rotor of the induction motor rotates faster than the stator rotating field so that negative slip occurs and the machine supplies energy. Thus, we need a device that can increase and decrease the voltage of this energy so that it can be stored in the battery. Therefore, in this study the SEPIC topology converter will be used. SEPIC (Single Ended Primary Inductor Converter) is a type of converter that can work step up or step down by setting the duty cycle on the gate switch. By conducting research on the design of the SEPIC converter as a battery charger using PID control which has a function so that the system achieves the desired response, it is hoped that charging can be carried out whose output can match the battery specifications. In this study, software was used to test the system, namely MATLAB/Simulink with the grid frequency as the independent variable. The test results show that the input from the SEPIC converter has varying values such as the voltage above or below 14V. The output of the SEPIC converter voltage has an error and the battery SoC also varies at each grid frequency that supplies the induction motor with a range of 10 Hz – 100 Hz. Keywords: Regenerative Braking, Three-Phase Induction Motor, SEPIC Converter, PID Control, State of Charge (SoC), MATLAB/Simulink